Evaluation of 20 pea lines (Pisum sativum L.) and their reaction to Ascochyta complex - Valencia A., Angelly; Timaná Ch., Yeily; Checa C., Oscar (Revista de Ciencias Agrícolas, 2013)
This investigation was made at Lope, SENA’s farm (National Service of Learning), in Pasto, Colombia, in order to evaluate pea genotypes (Pisum sativum) for yield and reaction to pathogens Ascochyta pisi and Mycosphaerella pinodes (A. pinodes). The design was complete randomized blocks with split plot arrangement, main plot included plant disease control (with and without control) and subplots 20 lines of pea. Variables evaluated were: days to flowering (FD), days to green harvest (HGD), pod number per plant (NPP), weight of grain pod (PWG), grain weight (WG), yield Y) and reaction to Ascochyta spp. Results showed that chemical application of the mixture Mancozeb and Benomyl fungicides affected pathogen development, reducing significantly the severity percentage in some lines, without affecting the yield. Lines UN7364, UN7313, UN7232-1 and UN7115 showed a moderately resistant reaction (MR) to A.pisi, while lines UN7100 and UN7232-1 were the best rated. The most affected line by pathogen complex was ILS3593. Respect to yield components better lines were UN7364 for (NPP), ILS3595for (PWG) and ILS3593 and ILS3594 for (WG); no line outperformed the yield of check lines, Andino and Sindamanoy.